The Ideas of Tolstoyism in Lithuania - Masionienė, Birutė (Problemos, 1970)
There is so far no special work on the spreading of Tolstoy’s religious-ethical ideas and their influence on the Lithuanian community. This subject, however, is of great interest both for literary critics and for investigators of the Lithuanian social thought. The author attempts to fill up the gap. The article provides little known information (the part of which is of the first printing) about the personal relations of Lithuanian Tolstoyans and Russian writer, about the movement of Tolstoyans in Lithuania (the beginning of the 20th century) which manifested itself through publication of newspapers, translation and publication of the writer’s works, origanization of the agricultural commune, etc.